Topsensterols A–C, Cytotoxic Polyhydroxylated Sterol Derivatives from a Marine Sponge Topsentia sp. - Chen, Min (Mar Drugs, 2016)
Three new polyhydroxylated sterol derivatives topsensterols A–C (1–3) have been isolated from a marine sponge Topsentia sp. collected from the South China Sea. Their structures were elucidated by detailed analysis of the spectroscopic data, especially the NOESY spectra. Topsensterols A–C (l–3) possess novel 2β,3α,4β,6α-tetrahydroxy-14α-methyl Δ(9(11)) steroidal nuclei with unusual side chains. Compound 2 exhibited cytotoxicity against human gastric carcinoma cell line SGC-7901 with an IC(50) value of 8.0 μM. Compound 3 displayed cytotoxicity against human erythroleukemia cell line K562 with an IC(50) value of 6.0 μM.